2006
DOI: 10.1124/dmd.106.009662
|View full text |Cite
|
Sign up to set email alerts
|

REGULATION OFCYP1A1GENE EXPRESSION BY THE ANTIOXIDANTTERT-BUTYLHYDROQUINONE

Abstract: ABSTRACT:CYP1A1, a major phase I enzyme, plays an important role in the metabolism of polycyclic aromatic hydrocarbons and in the chemical activation of xenobiotics to carcinogenic derivatives. The phenolic antioxidant tert-butylhydroquinone (tBHQ), often used as a food preservative, is generally considered to act only as a monofunctional inducer of phase II enzymes, thereby exerting chemoprotection. However, we recently observed that tBHQ elevated the activity of an aryl hydrocarbon receptor (AhR) response el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
23
1
Order By: Relevance
“…Some phase II enzymes are reported to be induced by tBHQ via the AhR pathway (Schreiber et al, 2006). To test the induction potential of tBHQ in rat intestine, we incubated slices (small intestine and colon) with tBHQ (50 M) for 0, 5, and 24 h, after which slices were incubated for 3 h with 7HC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some phase II enzymes are reported to be induced by tBHQ via the AhR pathway (Schreiber et al, 2006). To test the induction potential of tBHQ in rat intestine, we incubated slices (small intestine and colon) with tBHQ (50 M) for 0, 5, and 24 h, after which slices were incubated for 3 h with 7HC.…”
Section: Resultsmentioning
confidence: 99%
“…The AhR pathway is known to be involved in the induction of both phase I ( (Schreiber et al, 2006) has been reported to induce UGT activity in Caco-2 cells (Munzel et al, 1999), and, indeed, it induced glucuronidation in small intestine but not in colon slices. However, two other AhR ligands, 3MC and bNF, did not induce 7HC conjugation via UGT1A6 (Ikushiro et al, 2004) or UGT1A7/8 (Webb et al, 2005), which is in line with reported findings that UGT1A6 -8 mRNA expression was not induced in rat duodenum after in vivo administration of bNF (Shelby and Klaassen, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatoma cells were transfected with a firefly luciferase reporter plasmid containing three copies of the DRE3 motif (Kress et al, 1998) from the human CYP1A1 promoter (Schreiber et al, 2006) using Lipofectamine 2000 (Invitrogen, Karlsruhe, Germany). Plasmid pRL-CMV (Promega, Madison, WI) expressing Renilla luciferase under the control of the constitutively active cytomegaly virus promoter was cotransfected.…”
Section: Methodsmentioning
confidence: 99%
“…Induction of a wide range of antioxidative potentials such as elevation of the glutathione levels and GSTs, via the activation of ARE, was believed to be responsible for the protective effect of tBHQ [8]. Furthermore, Gharavi and El-Kadi [9], and Schreiber et al [10] demonstrated that tBHQ could also induce Phase I XMEs, cytochrome P450 1A1 (CYP1A1) gene expression directly in an aryl hydrocarbon receptor (AHR)-dependent manner in murine and human hepatoma cells. However, only limited information is available about the potential influence of tBHQ on DA metabolism in fish.…”
mentioning
confidence: 99%